2014
DOI: 10.1097/nna.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

BSN Completion Barriers, Challenges, Incentives, and Strategies

Abstract: Exploring RN barriers/challenges and incentives/supports for BSN completion can lead to implementation of institutional strategies, such as tuition reimbursement and academic collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 9 publications
4
61
0
Order By: Relevance
“…This finding is consistent with that of other major studies (Altmann, 2011;Duffy, Friesen, Speroni, & Swengros, 2014;Plunkett et al, 2010). H. Aiken et al, 2010;Institute of Medicine, 2011;Queensland Health, 2013).…”
Section: Supportsupporting
confidence: 82%
“…This finding is consistent with that of other major studies (Altmann, 2011;Duffy, Friesen, Speroni, & Swengros, 2014;Plunkett et al, 2010). H. Aiken et al, 2010;Institute of Medicine, 2011;Queensland Health, 2013).…”
Section: Supportsupporting
confidence: 82%
“…Students reported difficulty with navigating the university system, such as setting up e-mail accounts, utilizing the learning management system, and accessing library resources. Duffy et al (2014) also found that students reported similar difficulties, including difficulty with technology, such as computers, which was a barrier to students starting an RN-BSN program. Although some students reported that the workload was difficult to manage, many seemed to be okay with the workload and the class meetings, as long as they were meaningful and helped advance their learning.…”
Section: Suggestions For Improvementmentioning
confidence: 81%
“…Although some students reported that the workload was difficult to manage, many seemed to be okay with the workload and the class meetings, as long as they were meaningful and helped advance their learning. As suggested by Duffy et al (2014), in order to address these difficulties, a day-long new student orientation will be held before classes start to help students set up their e-mail accounts and log into their courses. The university librarian plans to conduct a library orientation session, and the success advisor will present a session on time management and stress management.…”
Section: Suggestions For Improvementmentioning
confidence: 99%
“…The counselor provides the necessary knowledge and preparation for navigating the transfer process between institutions or back into the academic environment. Many practicing nurses who have been away from the academic environment encounter changes in technology, questions about transfer credits and an unfamiliarity with higher education requirements which can cause anxiety and stress when returning to school [12]. To help students overcome challenges with academic progression, the admission counselor's goal is to build a close working relationship.…”
Section: Admission Counselormentioning
confidence: 99%